Understanding the mechanisms of dormancy in an invasive alien Sycamore lace bug, Corythucha ciliata through transcript and metabolite profiling - Feng-Qi Li (Nature Portfolio, 2017)
Abstract The sycamore lace bug, Corythucha ciliata, is a pest of sycamore trees. In China, it is found in the most northern border where it has been known to become dormant during harsh winters. But the molecular and metabolic basis for dormancy in this insect is still unknown. In this study, we analyzed the transcript and metabolite profiles of this bug to identify key genes and metabolites that are significantly regulated during dormancy in adult females and males. In total, 149 differentially expressed genes (DEGs) were significantly up-regulated and 337 DEGs were significantly down-regulated in dormant adults (both females and males). We found major differences in heat shock protein (HSPs), immunity-responsive genes, NAD-dependent deacetylase sirtuin-1 (SIRT1) and genes involved in the spliceosome pathway that is known to regulate stress. Among the 62 metabolites identified by GC-MS, 12 metabolites including glycerol, trehalose, and alanine were significantly increased during C. ciliata dormancy. By integrating the transcriptome and metabolite datasets, we found that the metabolites in glycolysis/gluconeogenesis and citrate cycle (TCA) were significantly reduced. This study is the first to report both transcript and metabolite profiles of the overwintering responses of C. ciliata to cold stress at the molecular level.